Growth of Banana-Based Agribusiness in Indonesia - Haryono, Haryono (West Science Interdisciplinary Studies, 2024)
This study examines the effects of market access, product innovation, and entrepreneurial experience on the growth of banana-based agribusinesses in Indonesia. Given the sector's significant potential in rural economic development, understanding the factors that drive agribusiness growth is essential. Using a quantitative approach, data were collected from 120 banana-based agribusinesses across various regions in Indonesia, with respondents rating each variable on a Likert scale of 1 to 5. Analysis was conducted using SPSS version 26, applying multiple regression to assess the significance and strength of each variable’s impact on business growth. Results indicate that market access, product innovation, and entrepreneurial experience each positively influence agribusiness growth, with product innovation emerging as the most significant predictor. These findings underscore the importance of market accessibility, continuous product innovation, and experienced entrepreneurship as key drivers of success in the agribusiness sector. This study provides actionable insights for policymakers and practitioners to enhance agribusiness performance through targeted support for market infrastructure, innovation, and entrepreneurial development.